Proceedings of the Ocean Drilling Program, 138 Scientific Results 1995
DOI: 10.2973/odp.proc.sr.138.156.1995
|View full text |Cite
|
Sign up to set email alerts
|

Strontium Isotopes in Pore Waters of East Equatorial Pacific Sediments: Indicators of Seawater Advection through Oceanic Crust and Sediments

Abstract: Pore-water samples from the equatorial sedimentary bulge area show reversals in depth profiles of 87 Sr/ 86 Sr ratios at the sedimentfàasement interface. Results of this work support inferences made from previous pore-water data (from DSDP drilling in the area) that large-scale horizontal advection of seawater has occurred through the basement underlying the thick sedimentary sequence in this region. The area of apparent advection includes the eastern part of the equatorial high-productivity zone and part of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 30 publications
(35 reference statements)
2
17
0
Order By: Relevance
“…4C), but the return to seawater values near basement is evidence of effi cient ventilation (Oyun et al, 1995). Site 846/1226 pore waters at the base of the sediments had detectable nitrate and also had a reversal of Sr, but concentrations differed from seawater values (Oyun et al, 1995). Overall these data indicate ventilated conditions at both sites, Site 1225 being better ventilated than 1226.…”
Section: Resultsmentioning
confidence: 83%
See 2 more Smart Citations
“…4C), but the return to seawater values near basement is evidence of effi cient ventilation (Oyun et al, 1995). Site 846/1226 pore waters at the base of the sediments had detectable nitrate and also had a reversal of Sr, but concentrations differed from seawater values (Oyun et al, 1995). Overall these data indicate ventilated conditions at both sites, Site 1225 being better ventilated than 1226.…”
Section: Resultsmentioning
confidence: 83%
“…In the center of the sediment column, Sr increases due to recrystallization of biogenic carbonate sediments (Fig. 4C), but the return to seawater values near basement is evidence of effi cient ventilation (Oyun et al, 1995). Site 846/1226 pore waters at the base of the sediments had detectable nitrate and also had a reversal of Sr, but concentrations differed from seawater values (Oyun et al, 1995).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As modeled by Yool and Tyrrell (2005), the oceanic response to an increased dissolved silica supply would have been much faster than that proposed by McGowran (1989). Moore (2008) proposed that the explanation for the widespread abundance of cherts in pelagic sections of the Pacifi c-especially at relatively shallow subbottom depths-lies in the circulation of hydrothermal waters in the upper oceanic crust (e.g., Baker et al, 1991;Oyun, et al, 1995;Fisher et al, 2003;Davis and Becker, 2004;Fisher, 2004;Bekins et al, 2007;Moore et al, 2007). Such waters can dissolve biogenic silica in the basal pelagic sections that form an imperfect aquitard over the crust and reprecipitate the silica in these sections as the waters conductively cool (Moore, 2008).…”
Section: Introductionmentioning
confidence: 97%
“…In the eastern Equatorial Pacific, it has long been recognized that surface conductive heat flow is significantly lower than theoretically predicted [ Langseth et al , 1965; Sclater et al , 1980]. Recent geochemical studies in pore waters have concluded that large quantities of seawater may have intruded below thick sediments thereby accounting for the anomalously low heat flow in this area [ Baker et al , 1991; Oyun et al , 1995; Spivack and You , 1997]. The chemical compositions of the deepest pore waters are similar to the present‐day seawater in Ca, Mg, SO 4 −2 , Sr and 87 Sr/ 86 Sr, suggestive of a short water residence time and minimum water‐rock interaction within the basement.…”
Section: Introductionmentioning
confidence: 99%